2019
DOI: 10.1002/anie.201906245
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Control of the Kinetic Propylene/Propane Separation by Zeolitic Imidazolate Framework‐8

Abstract: One intriguing feature of many porous MOFs is their stimulus-induced flexibility,w hichm akes them unique compared to standarda dsorbents.H ere we propose an innovative concept to achieve an efficient kinetic separation of species with similar properties by the mechanical fine-tuning of the pore architecture of the flexible zeolitic imidazolate framework ZIF-8. This unprecedented approach was applied to one of the most challenging societally relevant separations: the separation of propylene and propane,w hich … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 33 publications
1
34
0
Order By: Relevance
“…The porous nature of this family of compounds as well as their structural diversity has led to a wide range of potential applications being investigated. The properties of these materials which could lead to applications include: gas adsorption/separation [ 1 , 2 , 3 , 4 ], catalysis [ 5 , 6 ], drug delivery and biomedicine [ 7 , 8 ], photoluminescence sensors [ 9 , 10 , 11 , 12 , 13 ], magnetism [ 14 , 15 , 16 , 17 ], proton conductivity [ 18 , 19 , 20 , 21 ], or mechanical energy storage, among others [ 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 ]. Prior to its further use for an application, significant effort must be devoted to the characterization of the thermal and mechanical stability of MOFs [ 41 , 42 ].…”
Section: Introductionmentioning
confidence: 99%
“…The porous nature of this family of compounds as well as their structural diversity has led to a wide range of potential applications being investigated. The properties of these materials which could lead to applications include: gas adsorption/separation [ 1 , 2 , 3 , 4 ], catalysis [ 5 , 6 ], drug delivery and biomedicine [ 7 , 8 ], photoluminescence sensors [ 9 , 10 , 11 , 12 , 13 ], magnetism [ 14 , 15 , 16 , 17 ], proton conductivity [ 18 , 19 , 20 , 21 ], or mechanical energy storage, among others [ 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 ]. Prior to its further use for an application, significant effort must be devoted to the characterization of the thermal and mechanical stability of MOFs [ 41 , 42 ].…”
Section: Introductionmentioning
confidence: 99%
“…A more systematic computational exploration of diverse mechanical-constrained separations in a series of flexible and breathing MOFs is ongoing, for example, the typical case of propane/propylene kinetic separation in ZIF-8. [39] This will be further validated in the future with the development of a lab prototype that will allow the exploration of the separation processes under mechanical constraint.…”
Section: Resultsmentioning
confidence: 99%
“…As such, we have shown that the application of mechanical pressure can be used to tune the coadsorption behavior of mixtures in breathing MOFs, specifically with respect to the occurence of NGA and gas separation. A more systematic computational exploration of diverse mechanical‐constrained separations in a series of flexible and breathing MOFs is ongoing, for example, the typical case of propane/propylene kinetic separation in ZIF‐8 . This will be further validated in the future with the development of a lab prototype that will allow the exploration of the separation processes under mechanical constraint.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast to the effective pore aperture (4.0-4.2 )o f crystalline ZIF-8, the average pore diameter of a m ZIF-8 is be-tween the molecular kinetic diameters of CO 2 (3.3 )a nd N 2 (3.6 ), exhibiting the reduced gate size of a m ZIF-8 analogous to the simulation result. [15] Thus, the CO 2 /N 2 selectivity of a m ZIF-8 membrane was beyondt he reported polycrystalline ZIF-8 membranes (Table S3). Besides, the a m ZIF-8 membrane outperformed most of the polycrystalline ZIF-8 membranes in H 2 /CH 4 and CO 2 /CH 4 separation as well.…”
mentioning
confidence: 82%
“…[14] Very recently,M aurin and Zhenginvestigated the effect of external pressure on the kinetic separation of flexible ZIF-8 by molecular simulations. [15] The application of the mechanical pressure was revealed to control the pore size/shape of crystalline ZIF-8, which resulted in asignificant enhancement in its C 3 H 6 /C 3 H 8 diffusions electivity.Inspired by the implication of the separation abilityo famor-phousZ IF-8 (a m ZIF-8), we explored the adsorption property of a m ZIF-8 and offered ad irect insight into the effect of structural variationong as separation(Scheme 1).…”
mentioning
confidence: 99%